Enhancement of Magnetic Properties of La-substituted Strontium Hexaferrite Particles Prepared by Sol-gel Route - Nga, Tran Thi Viet; Duong, Nguyen Phuc; Hien, Than Duc (Communications in Physics, 2012)
La-substituted strontium hexaferrite particles Sr_1 - xLa_xFe_12O_19 (x = 0 0.2) were prepared by using sol-gel method and subsequent calcination at temperatures ranging from 750C to 1050C for 2h in air. The effects of the initial La concentration and the calcination temperature on the structure, particle morphology and magnetic properties of the hexaferrite samples were investigated by using X-ray diffraction (XRD), scanning electron microscopy (SEM) and vibrating sample magnetometer (VSM). The high magnetic coercivity (_iH_c) of 6.6 - 6.7 kOe and magnetization in maximum applied magnetic field (13.5 kOe) of 68 - 72 emu/g were achieved with the particles of compositions x = 0.1 0.2 and calcination temperatures between 850C and 1000C. The experimental data indicate that La replacement for Sr improves the crystallinity and inhibits the grain growth of the samples in a wide range of calcination temperature. These factors are important for production of high-coercivity hexaferrites by sol-gel technology.